PEMBELAJARAN SASTRA YANG MENARIK DAN MENYENANGKAN - Maria Derang Peuuma; Agung Pranoto; Rini Damayanti (sarasvati, 2022)
The need for learning literature in schools is a must, including in triggering, encouraging and motivating students to love and love learning literature. For this reason, superior literary works need to be introduced to students as a form of motivation for students in improving students' literacy skills. The aim of this research is to describe and apply a new paradigm around student learning in schools. This research uses qualitative method through literature study. The results showed that the new paradigm applied in learning literature in schools was as follows: (1) in learning literature the students looked very happy, happy and impressed pleasant, (2) students had the ability to read literary works such as poetry,short stories, novels, plays and live essays, . The most important aspect that must be studied in learning literature is the character of students, noble values and noble character. Thus, teachers, parents and children must synergize, be creative and innovative in realizing interesting and fun literary learning.